2021
DOI: 10.3390/plants10020237
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Biological Activity of Hennosides—Glucosides Isolated from Lawsonia inermis (henna): Could They Be Regarded as Active Constituents Instead

Abstract: Henna is the current name of the dye prepared from the dry leaf powder of Lawsonia inermis (Lythraceae). Several studies have focused on the chemistry and pharmacology of the henna dyeing active compound, lawsone, obtained from the main constituents of leaves, hennosides, during the processing of plant material. However, knowledge regarding the biological activity of hennosides is largely lacking. In this paper, the redox activity of three hennoside isomers is reported. The pro-oxidative activity was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Immediate soaking time delivers an 'a' value of around 10.0 units and reaches the maximum after 4 hrs of soaking at 14.0 units and then gradually decreased. Similar kinds of observations were reported by Maslovarić et al 13 , their findings indicated that releasable lawsone readily reacts with nitrogenous compounds such as amino acids, proteins etc. Elimination of nitrogenous materials is a critical step towards the stabilization of the lawsone molecule in the extract.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Immediate soaking time delivers an 'a' value of around 10.0 units and reaches the maximum after 4 hrs of soaking at 14.0 units and then gradually decreased. Similar kinds of observations were reported by Maslovarić et al 13 , their findings indicated that releasable lawsone readily reacts with nitrogenous compounds such as amino acids, proteins etc. Elimination of nitrogenous materials is a critical step towards the stabilization of the lawsone molecule in the extract.…”
Section: Resultssupporting
confidence: 86%
“…Elimination of nitrogenous materials is a critical step towards the stabilization of the lawsone molecule in the extract. Many authors work towards the lawsone extraction with various organic solvents to remove the nitrogenous compounds 11,13,15,17,20,21 3). The entire lawsone release study is immensely useful to draw the plot of optimized time recommendations for consumer practices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A study conducted by Pamunuwa et al 20 reported the antidiabetic, as well as antioxidant potential of lawsone (2-hydroxy-1,4-naphthoquinone), an aglycone, obtained from a glycoside (hennosides) during the chemical processing of Lawsonia inermis leaves. [21][22][23][24] Several studies reported that lawsone possesses various medicinal properties, including antimicrobial, antiparasitic, antioxidant, anti-inflammatory, antidiabetic, and anticancer activities. 21,24 The anti-hyperglycemic effect of L. inermis crude extract has been widely studied in the STZand AL-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, juglone (5‐hydroxy‐1,4‐naphthoquinone) has been documented to possess antidiabetic activity against diabetic mice 16 . A study conducted by Pamunuwa et al 20 reported the antidiabetic, as well as antioxidant potential of lawsone (2‐hydroxy‐1,4‐naphthoquinone), an aglycone, obtained from a glycoside (hennosides) during the chemical processing of Lawsonia inermis leaves 21–24 . Several studies reported that lawsone possesses various medicinal properties, including antimicrobial, antiparasitic, antioxidant, anti‐inflammatory, antidiabetic, and anticancer activities 21,24 .…”
Section: Introductionmentioning
confidence: 99%